The Role Generative AI in Human Resource Management: Enhancing Operational Efficiency, Decision-Making, and Addressing Ethical Challenges - Khan, Muhammad Inzamam; Parahyanti, Endang; Hussain, Shah (Asian Journal of Logistics Management, 2024)
This paper examines the use of generative AI in human resource management (HRM), emphasizing the improvement of operational efficiency and decision-making processes. The study used a literature based approach, combining information from peer reviewed journals, books, research articles and industry reports to examine the adoption of AI into HR tasks, such as recruiting, employee engagement, and performance management. This research demonstrates that generative AI significantly enhances recruiting by decreasing the time to hire and more precisely matching applicants with job specifications. Moreover, AI-driven technologies strengthen employee engagement by personalizing interactions and automating routine tasks, enabling HR professionals to concentrate on key objectives.The study's uniqueness is in its thorough assessment of the ethical dilemmas and challenges related to generative AI, including algorithmic bias and privacy issues. To address these dangers, the study emphasizes the need to include justice and openness in AI deployment. The results indicate that while generative AI has the potential for significant efficiency improvements, ethical governance is essential for its appropriate use.For strategic workforce management, HR managers must use generative AI while also being aware of ethical constraints. However, there are certain limitations, such as relying solely on current literature and the potential biases inherent in these sources. Subsequent research needs to concentrate on empirical validation and the formulation of frameworks to direct ethical AI implementation in human resources. This paper offers a comprehensive view of the advantages and obstacles associated with the integration of generative AI in HRM, highlighting the need for responsible and balanced implementation.